The Incidence of Hypoglycemia in Type 2 Diabetes Mellitus Patients - Jalal Khan, Syedda Alia Hassan Bukhari, Zahoor Ahmed Shah, Tuba Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To estimate the incidence of hypoglycemia in type 2 diabetes mellitus patients. Study design: Cross-sectional analytical study. Place and duration of study: Department of Medicine, Bolan Medical College, Quetta from 1st January 2021 to 30th September 2021. Methodology: One hundred type 2 diabetic patients were enrolled. Each patient complete detail was documented on a well-structured questionnaire which was also used for assessing the hypoglycemia status using Whipple’s triad questionnaire based information. The Whipple triad is an assembly of three criteria named as Whipple’s criteria. The most important symptoms which are presented in it are those symptoms which show presentation of hypoglycemia post meal and exercise. Patients were asked for any of the following symptoms or biochemical test results have been noticed in previous 2-3 months and their responses were recorded. Results: There were 64% patients within the age of 40-60 years while 36% were above the age of 60 years. Within the rural, type 2 diabetic patients 89.3% were those who only checked their glucose once in three months. The treatment method which was adapted by majority of the type 2 diabetic patients was use of metformin. Conclusion: Hypoglycemia appeared to be the important determinant of diabetes mellitus and sometime even prove more fatal then hyperglycemia.